IMPLEMENTASI PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH(BOS) UNTUK PENGEMBANGAN GURU DAN FASILITAS SEKOLAH DI SMP KOTA SEMARANG - Refgi Septian; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
ABSTRACT The implementation of School Operational Assistance (BOS) is one of the government policies to aimed at improving the quality of education for all levels of society by funding school operation activities. But School Operational Assistance (BOS) funds can also be used to other thing, that is teacher development and school facilities in the teacher profession development component, education staff and scholl management development, while for school facilities in the maintenance of infrastructure facilities and the multimedia learning tool component. However, not all school met all components of BOS funds, including components for teacher development and school facilities The research was conducted in Semarang City Middle Schools namely SMP Negeri 1, 2 and 19 Semarang City. The research was conducted based in the implementation not meet all the components of BOS. especially the teacher development component and school facilities components. The purpose of this study is to describe and analyze the implementation of school operational assistance (BOS) funds for teacher development and school facilities in Semarang City Junior High Schoold and to identify and analyze the factors that influence the implementation of school operational assistance (BOS) funds for teacher developments and school facilities in Semarang City Middle School. The researcher uses the van Meter and van Horn Implementation model with top-down approach. Based on research, the implementation of school operational assistance (BOS) funds for teacher development and school facilities is still not optimal, due to the influence of standar and objective factor which is lack of certainty and judgment in using teacher development and school facilities components and there is no reward given to school for maximizing the use of BOS funds to provide a stimulus for schools as implementor